A 2.4 GHz receiver with a current-reused inductor-less noise-canceling balun LNA in 40 nm CMOS. (July 2021) - Liu, Xiaoming; Jin, Jing; Wang, Xiaofei; Zhou, Jianjun
Abstract: A low power receiver is designed and implemented for 2.4 GHz Industrial-Scientific-Medical (ISM) band in a 40 nm CMOS process. To obtain good noise and linearity performance at low cost, a current-reused low power inductor-less balun low noise amplifier (LNA) structure is proposed without use of monolithic spiral inductors or transformers. The receiver adopts a zero-IF architecture and current mode mixing operation which avoid need of large voltage headroom for the radio frequency (RF) voltage swing under strong interferers. A third order active-RC low pass filter (LPF) with RC calibration and DC offset cancelation (DCOC) blocks are carefully designed. Current reusing technique and timing optimized asynchronous SAR logic are adopted in LNA and ADC design respectively, featuring high-power efficiency. The total receiver chain achieves maximum conversion gain of 80.32 dB, noise figure (NF) of 6.27 dB and input referred third-order intercept point (IIP3) of −0.6 dBm with 32.8 mW power consumption.